2019
DOI: 10.1177/0269215519840403
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Lycra® orthoses as an adjunct to arm rehabilitation after stroke: a single-blind, two-arm parallel group, randomized controlled feasibility trial

Abstract: Objective: The aim of this study was to explore the feasibility of conducting a randomized controlled trial of dynamic Lycra® orthoses as an adjunct to arm rehabilitation after stroke and to explore the magnitude and direction of change on arm outcomes. Design: This is a single-blind, two-arm parallel group, feasibility randomized controlled trial. Setting: In-patient rehabilitation. Subjects: The study participants were stroke survivors with arm hemiparesis two to four weeks after stroke receiving in-patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…These adaptations may partly explain findings of the feasibility trial, which indeed showed no indications of benefits of dynamic Lycra® orthoses on arm recovery in this population. 6 Any intervention adaptations need to be considered against the backdrop of "the fidelity and adaptation debate" 4 (p.39). This debate calls for a distinction between 'innovation', whereby skilled implementers adapt an intervention to better fit the context, and 'drift', whereby adaptations could potentially undermine an intervention's effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These adaptations may partly explain findings of the feasibility trial, which indeed showed no indications of benefits of dynamic Lycra® orthoses on arm recovery in this population. 6 Any intervention adaptations need to be considered against the backdrop of "the fidelity and adaptation debate" 4 (p.39). This debate calls for a distinction between 'innovation', whereby skilled implementers adapt an intervention to better fit the context, and 'drift', whereby adaptations could potentially undermine an intervention's effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Because of attrition, sub-groups were however too small for meaningful conclusions. 6 It is similarly unclear whether responses to orthosis wear might vary depending on when the orthosis is worn (eg, outside or during task practice). We prescribed orthosis wear for 8 h daily, according to manufacturer's guidance, intending that the orthosis would be worn during the most active parts of the day, including during task practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, not covering the elbow joint could be a problem, as a published review 29 showed that spasticity is one of the major contributors that limit the arm movement after stroke at the elbow joint. The pressure garment wearing time was decided upon our review on published studies 14,16 with the suggestion that at least 6 hour/day stretching may be needed to prevent a muscle from developing into a contracture. Since we only referenced scar control guidelines when designing and fabricating the pressure garment, we could not ascertain if these guidelines were also suitable for use in stroke management.…”
Section: Discussionmentioning
confidence: 99%
“…2,13 To our knowledge, there were two studies that had investigated the effects of pressure garment on spasticity and arm function in stroke. 4,14 Gracies et al, 4 while investigating the effect of Lycra glove in hemiplegic individuals, found that the glove can improve wrist posture, reduce wrist and finger flexor spasticity, swelling in fingers, and improve passive range of movement in the shoulder. Morris et al, 14 most recently, found that there was a low retention rate of patients with dynamic Lycra orthoses with some having adverse reactions.…”
Section: Introductionmentioning
confidence: 99%